The Body as a Toolbox in the Hausa Language - Yusuf, Aliyu Yalubu (AAeO - Afrikanistik-Aegyptologie-Online, 2021)
This paper discusses Hausa proverbs related to body parts and bodily functions. The Hausa people sometimes conceptualize body-related proverbs as tools used to perform certain functions virtually or in reality. Thus, this study attempts to explore some of these proverbs and analyze them within the framework of Linguistic Relativity, nowadays associated with Edward Sapir and Benjamin Lee Whorf. Through the use of a purposive sampling pro-cedure, the data (the proverbs) for the study is generated from a written textbook on Hausa proverbs and from non-participant observation of spontaneous communication among Hausa native speakers in Kano state, Nigeria. From the analysis of the selected proverbs, the study found out that Hausa people have a penchant of conceptualizing body parts as tools. And this further reinforces the belief that although in the Western world, some of the works associated with human body are, to a large extent, done by machines these days, in Africa, human body parts are still used as tools to perform a number of functions, hence their linguistic conceptualization as such.